Effectiveness of 100 Beats per Minute Music on Cardiopulmonary Resuscitation Compression Rate Education: A Manikin Study. Issue 1 (January 2017) - Kim, KW; Kim, JH; Choe, WJ; Kim, JY; Lee, SI; Kim, KT; Park, JS; Kim, JW; Lee, Y; Lee, JH; Park, J
Introduction: Recent cardiopulmonary resuscitation (CPR) guidelines emphasize the importance of high-quality chest compression. The aim of this study is to determine the effect of education using music on the chest compression rate. Methods: This randomised, open-labeled study enrolled 81 medical students. They were randomly divided into three groups. After they were educated in CPR according to the American Heart Association 2010 guidelines, they performed 100 chest compressions using a mannequin capable of collecting each compression depth and speed. After that, the control group received a verbal feedback about their own results. The metronome group was also notified of their own results, and listened to the metronome sound at 100 beats per minute (bpm). The music group listened to the music (about 100 bpm). Twenty-four hours after their CPR education, chest compressions were performed again with the method identical to the first evaluation. The results were compared using multivariate analysis of variances. Result: Compression rate (bpm): There was a significant difference between the control (mean, 110.4; 95% CI: 104.4, 116.5) and metronome group (mean, 98.5; 95% CI: 91.6, 105.4) after education (p=0.01). There was a significant difference between control and music group (mean, 98.2; 95% CI: 94.6, 101.8) after education (p<0.001) There were no differences between the music and metronome group before or after education (p=0.50, p=0.94). However, the variance of music group was significantly less than the metronome group (p=0.01). Compression depth (inches): there was no difference between the groups according to the CPR education method. (Control: 1.8±0.3; Metronome group: 1.6±0.2; Music group: 1.7±0.3 p=0.09) Conclusion: Both education method of using music and metronome are more effective than conventional method. However the effect of using music may be better than using metronome.